Tingkat Kemampuan Vo2Max Pada Atlet Bola Basket Puteri POMNAS Riau - Oki Candra (Journal Sport Area, 2020)
The purpose of this study is to determine how far the extent of Vo2Max capability towards female basketball athletes in Riau National Police. This research is a quantitative descriptive study with the method that used in this study is a survey method that is the collecting data that using only tests and measurements. The population of this research is the POMNAS Riau female basketball athletes. The sample in this study is 15 people with a total sampling technique, where all populations are be samples. The data analysing technique that used is descriptive statistics that aimed for collecting data, presenting data, and determining score. The data that obtained from each test is the initial data from each test item that has been achieved. Referring to the data that have been obtained, from the final results of the study and discussion, it can be concluded that the level of Vo2Max ability of POMNAS Riau female basketball athletes by using the Balke testt, amount to 15 athletes are in the category of very little. For this reason, this research needs to be followed up in the future that a coach must have a structured and continuous program so that in future the results of Vo2Max of basketball athletes will be even better without experiencing significant exhaustion.